Cooperative bargaining to internalise open access externalities: Implications of the American fisheries act - Scott C. Matulich; Murat Sever; Fred Inaba (Fondazione Eni Enrico Mattei (FEEM), 2000)
The United States Congress recently passed a law that creates an alternative to individual transferable quota (ITQ) management. The American Fisheries Act promises the ability to rationalise one of the world's largest fisheries, the North Pacific pollock fishery, without the overt appearance of allocating permanent property rights to a public resource. The Act enabled pollock fishers to form cooperative bargaining units that are guaranteed a fixed share of the total allowable catch providing they deliver to historic processors. This paper explores the political economy of policy change and the innovative use of fishery cooperatives to advance voluntary decapitilisation and rationalisation that Congress intended to benefit both vessels and processors. Game theory offers insights into the likelihood of achieving congressional intent. It is argued that the Act introduces a new market failure while attempting to rid the fishery of the open access externality. It is further argued that outcomes of voluntary agreements, whether targeting environmental concerns or natural resource management, are sensitive to market structure and institutional contexts.
Keywords: Q22; D43; 330; Voluntary fishery cooperatives; rationalisation; non-cooperative game; market failure; Fischerei; Gemeingüter; Genossenschaft; Kooperatives Spiel; Verhandlungstheorie; Theorie; USA